Spatial tuning curves from apical, middle, and basal electrodes in cochlear implant users - Nelson, David A. (Acoustical Society of America, 2011)
Forward-masked psychophysical spatial tuning curves (fmSTCs) were measured in 15 cochlear-implant subjects, 10 using monopolar stimulation and 5 using bipolar stimulation. In each subject, fmSTCs were measured at several probe levels on an apical, middle, and basal electrode using a fixed-level probe stimulus and variable-level maskers. Tuning curve slopes and bandwidths did not change significantly with probe level for electrodes located in the apical, middle, or basal region although a few subjects exhibited dramatic changes in tuning at the extremes of the probe level range. Average tuning curve slopes and bandwidths did not vary significantly across electrode regions. Spatial tuning curves were symmetrical and similar in width across the three electrode regions. However, several subjects demonstrated large changes in slope and/or bandwidth across the three electrode regions, indicating poorer tuning in localized regions of the array. Cochlear-implant users exhibited bandwidths that were approximately five times wider than normal-hearing acoustic listeners but were in the same range as acoustic listeners with moderate cochlear hearing loss. No significant correlations were found between spatial tuning parameters and speech recognition; although a weak relation was seen between middle electrode tuning and transmitted information for vowel second formant frequency.